2013
DOI: 10.1007/s11205-013-0466-9
|View full text |Cite
|
Sign up to set email alerts
|

Smokers’ Sexual Behavior and Their Satisfaction with Family Life

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
2
2
0
Order By: Relevance
“…As expected, people are likely to place more weight on household-level SES factors, as well as subjective household-level SES, than on individual-level SES factors when assessing how satisfied they are with family life. The positive association between SES and satisfaction with family life is in a sense consistent with the findings of Agate et al (2009) and Yamamura (2014), who found a positive relationship between satisfaction with family life and income. However, the results are not directly comparable given this paper's use of broader SES indicators and not income only.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…As expected, people are likely to place more weight on household-level SES factors, as well as subjective household-level SES, than on individual-level SES factors when assessing how satisfied they are with family life. The positive association between SES and satisfaction with family life is in a sense consistent with the findings of Agate et al (2009) and Yamamura (2014), who found a positive relationship between satisfaction with family life and income. However, the results are not directly comparable given this paper's use of broader SES indicators and not income only.…”
Section: Discussionsupporting
confidence: 90%
“…", with responses recorded on a 5-point scale ranging from dissatisfied to satisfied. Yamamura (2014) found a positive relationship between the frequency of sex and satisfaction with family life, although this relationship as expected was significant for married persons but not unmarried persons. Furthermore, satisfaction with family life was positively related to income whereas the unemployed were less satisfied with family life compared to the employed.…”
Section: Literaturesupporting
confidence: 52%
See 1 more Smart Citation
“…Long-term addiction also unsettles the process of sexual satisfaction. As reported, the high rates of divorce are mostly associated with failure to establish high-quality marital relationships (Yamamura 2014). In view of this, SD can have detrimental effects on the collapse of the family, including aggressive marital conflicts and large gaps between couples (Binik & Hall 2014).…”
Section: Introductionmentioning
confidence: 99%